2015
DOI: 10.1016/j.chembiol.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Modulators of Methyl-Lysine Binding for the CBX7 Chromodomain

Abstract: SUMMARY Chromobox homolog 7 (CBX7) plays an important role in gene transcription in a wide array of cellular processes, ranging from stem cell self-renewal and differentiation to tumor progression. CBX7 functions through its N-terminal chromodomain (ChD), which recognizes tri-methylated lysine 27 of histone 3 (H3K27me3), a conserved epigenetic mark that signifies gene transcriptional repression. In this study, we report discovery of small molecules that inhibit CBX7ChD binding to H3K27me3. Our crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 22 publications
1
106
0
Order By: Relevance
“…Our study has revealed a novel mechanism of Notch epigenetic regulation in breast cancer. In light of the recent development of compounds that inhibit Cbx function (Ren et al, 2015, Simhadri et al, 2014, Stuckey et al, 2016), our studies provide support for targeting Cbx8 as an alternative strategy to attenuate Notch signaling in breast cancer. Specificity of inhibitory compounds for Cbx orthologues will be essential for such therapeutic targeting.…”
Section: Discussionmentioning
confidence: 58%
“…Our study has revealed a novel mechanism of Notch epigenetic regulation in breast cancer. In light of the recent development of compounds that inhibit Cbx function (Ren et al, 2015, Simhadri et al, 2014, Stuckey et al, 2016), our studies provide support for targeting Cbx8 as an alternative strategy to attenuate Notch signaling in breast cancer. Specificity of inhibitory compounds for Cbx orthologues will be essential for such therapeutic targeting.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies from the Zhou lab have reported weak, non-peptidic small molecule CBX7 ligands; however, SAR studies around these molecules struggled to produce significant improvements in potency. 21, 23 …”
Section: Resultsmentioning
confidence: 99%
“…Recent breakthroughs in biological and medical applications of small molecule antagonists for acetyllysine-binding bromodomain, methyllysine-binding MBT and chromodomain, and arginine-recognizing WD40 demonstrate the vast potential of targeting the histone readers (15)(16)(17)(18)(19)(20). A number of epigenetic inhibitors are in clinical trials as anticancer and antiinflammatory agents (15,21,22).…”
mentioning
confidence: 99%